Development Potential of Fisheries as a Maritime Activity in Supporting Area Planning - Budiati, Malinda; Sidabutar, Yuanita FD; Tanjung, Raflis; Bintang, Malahayati Rusli; Raymond, Raymond (Journal La Lifesci, 2024)
This paper aimed to identify and discuss the gains on the development of fishery, maritime tourism and community engagement towards the regional planning of Belakang Padang District in Indonesia. Based on both exploratory and explanatory qualitative and quantitative data collected for the study, the study establishes and examines the economic, cultural, and environment opportunities and barriers to region development in the district. The studies show that fisheries are the largest and most important economy sector that influences the planning of regions; at the same time, the challenges are observed in terms of outdated technique and restricted access to markets. Maritime tourism has a lot of prospects and long-term influences for countries but it is restricted by the lack of sufficient infrastructure and capital. The study also highlights a major research agenda concerning the lack of citizenship in planning where most of the local actors are rarely involved in planning processes. Environmental sustainability as an additional challenge was discovered with pollution together with the inadequate disposal of wastes contributing to the harm of the district’s development. Therefore, the study recommends an integrated regional development plan, focusing on the modernization of fisheries, tourism development, participation of community and conservation of the environment as key factors for sustainable development of Belakang Padang. Hence the research is useful in the existing literature on sustainable coastal development and charles district future planning activities.